2009
DOI: 10.1007/s10096-009-0851-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a procalcitonin algorithm to guide antibiotic therapy in respiratory tract infections outside of study conditions: a post-study survey

Abstract: All published evidence on procalcitonin (PCT)-guided antibiotic therapy was obtained in trials where physicians knew that they were being monitored, possibly resulting in higher adherence to the PCT algorithm. This study investigates the effectiveness of PCT guidance in an observational quality control survey. We monitored antibiotic therapy and algorithm adherence in consecutive patients with respiratory tract infections admitted to the Kantonsspital Aarau, Switzerland, between May 2008 and February 2009. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 18 publications
(37 reference statements)
3
38
1
5
Order By: Relevance
“…This result is likely due to the limited number of patients included in the study, and in general the impact of a PCT-based algorithm on the hospital stay in CAP is not yet known as shown in other studies, where the in-hospital length of stay was similar in the active group and controls. 10,13 Our results along with those of the above cited studies are appealing, and the way to minimize antibiotic treatment duration without affecting safety, may be an important issue to reduce hospital stay and costs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This result is likely due to the limited number of patients included in the study, and in general the impact of a PCT-based algorithm on the hospital stay in CAP is not yet known as shown in other studies, where the in-hospital length of stay was similar in the active group and controls. 10,13 Our results along with those of the above cited studies are appealing, and the way to minimize antibiotic treatment duration without affecting safety, may be an important issue to reduce hospital stay and costs.…”
Section: Discussionmentioning
confidence: 92%
“…This was an international, multicenter observational quality survey that showed a significant reduction in antibiotic exposure in the PCT group compared to the control group [5.9 vs 7.4 days; difference, -1.51 days; 95% confidence interval (CI), -2.04 to -0.98; P<0.001], with no risk increase in the combined adverse outcome end point within 30 days of followup when the PCT algorithm was followed regarding early cessation of antibiotics (adjusted odds ratio, 0.61; 95% CI, 0.36 to 1.04; P=0.07). 10 However, the population studied was heterogeneous with a prevalence of nearly 30% of acute bronchitis and acute exacerbations of chronic obstructive pulmonary disease, which are lower respiratory tract infections far less severe than CAP in hospitalized patients. Furthermore, disease severity assessed by CURB-65 in CAP patients in the study, was less than in a population of real-life CAP patients commonly observed and cared in medical wards (mean/median 1.1/0 vs 1.8/2 in our population).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It reaches its peak after 6 hours and has a half-life of 25 to 30 hours [13,23]. Some studies have shown the course of procalcitonin serum levels reflects the success of antibiotic treatment of bacterial infection rapidly, closely, and more reliably than CRP level [13,18,29,31,37].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [9][10][11] have indicated that procalcitonin is superior to other commonly used parameters in its specificity for bacterial infection and might help to guide antibiotic stewardship in lower respiratory tract infections. However, its role in critically ill patients is still disputed.…”
Section: Introductionmentioning
confidence: 99%